(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
This article examines the use of blogs to mediate the experiences of citizens during a violentelection in Zimbabwe. It focuses specifically on how people disseminated and shared informationabout their tribulations under a regime that used coercive measures in the face of its crumblinghegemonic edifice. The article frames these practices within theories of alternative media andcitizen journalism and argues that digitisation has occasioned new counter-hegemonic spacesand new forms of journalism that are deinstitutionalised and deprofessionalised, and whoseradicalism is reflected in both form and content. I argue that this radicalism in part articulates apostmodern philosophy and style as seen in its rejection of the elaborate codes and conventionsof mainstream journalism. The Internet is seen as certainly enhancing the people’s right tocommunicate, but only to a limited extent because of access disparities, on the one hand, and itsappropriation by liberal social movements whose configuration is elitist, on the other. I concludeby arguing that the alternative media in Zimbabwe, as reflected by Kubatana’s bloggers, lack thecapacity to envision alternative social and political orders outside the neo-liberal framework. This,I contend, is partly because of the political economy of both blogging as a social practice andalternative media as subaltern spaces. Just as the bloggers are embedded to Kubatana’s virtualspace to self-publish, Kubatana is likewise embedded to a neo-liberal discourse that is traceableto its funding and financing systems.